A Study of Protean Career Orientation and Organizational Commitment of Permanent and Contractual Faculty Teaching Professional Courses in Delhi - NCR - Khatri, Puja; Raina, Khushboo (Prabandhan: Indian Journal of Management, 2017)
The current working environment is complex and demands extraordinary efforts from faculty. They are expected to be loyal to the organization, multitask, and seek institutional support for skill development. However, with the introduction of new career concepts like 'protean career,' the attitude seems to have shifted, and the employees are registering a drop in commitment towards an organization. This vicious circle has to be tackled keeping in mind the personal growth of the faculty which can provide leverage to academic institutions. The concept of career has come a long way from being traditional to protean. Adaptation to new concepts is the key to success. The present study attempted to understand the relationship between protean career orientation, attitude towards multitasking, and organizational commitment of permanent and contractual faculty teaching professional courses in Delhi-NCR. Adapted and self constructed questionnaires were used for the study and had a reliability of 0.90. The study is quantitative as well as qualitative in nature where four experts each from public and private institutes were contacted for semi structured interviews regarding their views about certain findings of the study. Contrasting results were seen while analyzing differences between permanent and contractual faculty with regard to their protean career orientation and attitude towards multitasking. The study will be beneficial to the policy makers and administrators of professional institutions in Delhi-NCR and the academia at large.